Risk factors for reinvasion of human dwellings by sylvatic triatomines in northern Bahia State, Brazil - Annie Walter; Isabel Pojo do Rego; Agenor José Ferreira; Christophe Rogier (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2005)
The aim of this study in Curaça, Bahia, Northeast Brazil was to explore possible factors associated with the infestation of human dwellings by Triatoma brasiliensis or Triatoma pseudomaculata, two sylvatic triatomine species. We use multiple logistic regression analysis to show how structural features of the peridomiciliary area combine with the number of animals and sociological factors to allow infestation of some dwellings. It is suggested that T. brasiliensis is associated with human activities, while T. pseudomaculata is associated with vegetation and animals. Peridomiciliary farm animals are a strong risk factor for triatomine infestation.